2005
DOI: 10.1038/sj.jcbfm.9600077
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term in Vivo Investigation of Mouse Cerebral Microcirculation by Fluorescence Confocal Microscopy in the Area of Focal Ischemia

Abstract: This study was designed to assess that mouse pial and cortical microcirculation can be monitored in the long term directly in the area of focal ischemia, using in vivo fluorescence microscopy. A closed cranial window was placed over the left parieto-occipital cortex of C57BL/6J mice. Local microcirculation was recorded in real time through the window using laser-scanning confocal fluorescence microscopy after intravenous injection of fluorescent erythrocytes and dextran. The basal velocity of erythrocytes thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(99 citation statements)
references
References 22 publications
2
95
1
Order By: Relevance
“…Diameters of pial collaterals of B6 mice (measured under ketamine and xylazine anesthesia with intravital microscopy through an open cranial window) increase up to fivefold after topical adenosine or sudden increase in shear stress following acute MCAO . Others have reported that pial collaterals exhibit basal tone (Wei et al, 2001;Tomita et al, 2005). Inhibition of substantial basal tone in pial collaterals after MCAO could contribute to the rapid remodeling we observed, as chronic vasodilation is known to stimulate outward remodeling of arterioles (van Gieson et al, 2003).…”
Section: Discussionmentioning
confidence: 63%
“…Diameters of pial collaterals of B6 mice (measured under ketamine and xylazine anesthesia with intravital microscopy through an open cranial window) increase up to fivefold after topical adenosine or sudden increase in shear stress following acute MCAO . Others have reported that pial collaterals exhibit basal tone (Wei et al, 2001;Tomita et al, 2005). Inhibition of substantial basal tone in pial collaterals after MCAO could contribute to the rapid remodeling we observed, as chronic vasodilation is known to stimulate outward remodeling of arterioles (van Gieson et al, 2003).…”
Section: Discussionmentioning
confidence: 63%
“…For longitudinal experiments, the same anesthetics have been repeatedly used in single animals; i.e., isoflurane (Colonnese et al, 2008;Tomita et al, 2005) and ketamine/xylazine (Brown et al, 2010). For those experiments, good recovery from anesthesia discontinuation is important in the choice of anesthetics for performing controlled experiments.…”
Section: Other Considerationsmentioning
confidence: 99%
“…Direct brain imaging with better spatial (micrometric) and temporal resolutions can be obtained using optical techniques (Helmchen and Denk, 2005). Traditional fluorescence confocal laser scanning microscopy allows an imaging depth of about 200 mm in brain tissue with a high spatial resolution (Tomita et al, 2005) and this imaging depth had been extended with the development of multiphoton laser scanning microscopy, which became the main technique for high-resolution in vivo deep imaging (Denk et al, 1990). A imaging depth of 500-600 mm can be obtained currently in the cortex (Helmchen and Denk, 2005) (this covers around 70% of the mouse cortex) and imaging of brain vessels as deep as 1000 mm has been reported (Theer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%